The skin microbiome of caspase‐14‐deficient mice shows mild dysbiosis. Issue 8 (16th July 2014) - Kubica, Malgorzata; Hildebrand, Falk; Brinkman, Brigitta M.; Goossens, Dirk; Del Favero, Jurgen; Vercammen, Ken; Cornelis, Pierre; Schröder, Jens‐Michael; Vandenabeele, Peter; Raes, Jeroen; Declercq, Wim
Abstract Caspase‐14, an important proteinase involved in filaggrin catabolism, is mainly active in terminally differentiating keratinocytes, where it is required for the generation of skin natural moisturizing factors (NMFs). Consequently, caspase‐14 deficient epidermis is characterized by reduced levels of NMFs such as urocanic acid and 2‐pyrrolidone‐5‐carboxylic acid. Patients suffering from filaggrin deficiency are prone to develop atopic dermatitis, which is accompanied with increased microbial burden. Among several reasons, this effect could be due to a decrease in filaggrin breakdown products. In this study, we found that caspase‐14−/− mice show enhanced antibacterial response compared to wild‐type mice when challenged with bacteria. Therefore, we compared the microbial communities between wild‐type and caspase‐14−/− mice by sequencing of bacterial 16S ribosomal RNA genes. We observed that caspase‐14 ablation leads to an increase in bacterial richness and diversity during steady‐state conditions. Although both wild‐type and caspase‐14−/− skin were dominated by the Firmicutes phylum, the Staphylococcaceae family was reduced in caspase‐14−/− mice. Altogether, our data demonstrated that caspase‐14 deficiency causes the imbalance of the skin‐resident bacterial communities.